Pengaruh Pemahaman Perpajakan dan Keadilan Pajak Terhadap Persepsi Wajib Pajak Orang Pribadi Mengenai Penggelapan Pajak Dengan Religiusitas Sebagai Variabel Moderasi - Kurwanti, Syafina Sri; Anggraini, Dahlia Tri (Jambura Economic Education Journal, 2025)
In using religiosity as a moderating variable, this study attempts to examine how individual taxpayers' opinions of tax evasion are impacted by their knowledge of taxes and tax justice. This kind of study is quantitative and descriptive. There were 75 responders who were individual taxpayers at the Sawangan Depok Primary Tax Service Office. Purposive sampling combined with non-probability sampling is the strategy used in this study to gather data sources.The SmartPLS 4.0 version is the analytical tool utilized. The findings demonstrated that individual taxpayers' perceptions of tax evasion are significantly impacted by their sense of tax fairness and comprehension, and that the relationsip between these two factors and the perceptions of tax evasion can be moderated by religious belief (religiosity). Furthermore, it is advised that the study's factors be expanded for readers and upcoming scholars. Research can offer a more comprehensive and proficient comprehension of the several elements that may impact tax evasion by incorporating more variables.